Good video games + good learning : collected essays on video games, learning and literacy. - Gee, James Paul, 1948- (New York : Lang, 2007)
Inhoudsopgave : 1.Why video games are good for your soul: pleasure and learning.2.Video games, violence, and effects: good and bad.3.Notes on content and technological determinism.4.Good video games, the human mind, and good learning.5.Learning about learning from a video game: rise of nations.6.Pleasure and being a professional: learning and video games.7.Why study games now ? Video games: a new art form.8.Affinity spaces: from age of mythology to today's schools.9.Reading, specialist language development, and video games.10.Games and learning: issues, perils, and potentials.